Plant-soil feedbacks in Hydrocotyle vulgaris: Genotypic differences and relations to functional traits. (February 2023) - Begum, Ghazala; Gao, Jun-Qin; Xue, Wei; Yu, Fei-Hai
Highlights: We tested genotypic differences in plant-soil feedbacks (PSFs) in Hydrocotyle vulgaris . PSFs varied among genotypes of H. vulgaris in terms of direction and strength. Across genotypes of H. vulgaris, PSFs were correlated to plant functional traits. Genotypic differences in PSFs may influence population structure and dynamics. Abstract: Plant-soil feedbacks (PSFs) may vary among genotypes within the same species and may also be predicted by plant functional traits. So far, however, it is still unclear whether PSFs can be correlated with plant functional traits across genotypes of the same species. We conducted a two-phase PSF experiment with a clonal plant Hydrocotyle vulgaris . In the conditioning phase, we planted 12 genotypes of H. vulgaris separately in the soil. In the feedback phase, all these genotypes of H. vulgaris were grown again separately in each of the conditioned soil that was trained either by the same genotype (home soil) or by the other 11 genotypes (non-home soil). Most of the genotypes showed negative PSFs, as indicated by significant lower biomass and number of ramets in the home soil than in the non-home soil. However, there were also genotypes showing neutral PSFs as neither biomass nor number of ramets differed significantly between the home and the non-home soil or positive PSFs as biomass and number of ramets were higher in the home than in the non-home soil. In addition, we found a significant positive relationship between the PSF strength with lamina area, specific lamina area, petiole length, specific petiole length and internode length, but a negative relationship between the PSF strength and specific internode length. We conclude that the PSFs can vary among genotypes within the same species and negative PSFs are more common compared to positive PSFs. The results also highlight the role of plant functional traits in predicting PSFs across genotypes.